ISOLATION AND SCREENING OF L-ASPARAGINASE PRODUCING SPHINGOMONAS SP. FROM SOIL SAMPLE - DEEPAK VMM; L, VAISHNAVI; PALANISWAMY, RADHA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: In recent years, L-asparaginase has gained attention due to its anticancer activity. Different types of asparaginase possess different characteristics and different applications. The study is designed to screen potential L-asparaginase producing bacteria from soil samples. Methods: Soil samples were collected from different locations in Tamil Nadu and Kerala for the isolation of L-Asparaginase-producing bacteria. Results: About 689 isolates were obtained from 114 samples. Among these, 214 isolates possess the ability to synthesize L-asparaginase. Fifteen isolates were selected for quantitative screening based on the intensity of the pink color formation M9 basal medium. Conclusion: The isolate VN01 exhibited a higher degree of enzyme activity (156 IU/mg). The isolate was further categorized by phenotypic and genotypic method and the isolate was identified as Sphingomonas leidyi. As a future aspect, the study will be continued for optimization of increased production of L-asparaginase and in characterizing the potential of L-asparaginase synthesized by S. leidyi.